KEDUDUKAN BADAN NARKOTIKA NASIONAL DALAM STRUKTUR KETATANEGARAAN DI INDONESIA - Abdullah Abdullah (Maleo Law Journal, 2020)
Responding to the development of the drug problem which continues to increase and is increasingly serious, the MPR-RI Decree Number VI / MPR / 2002 through the General Session of the People's Consultative Assembly of the Republic of Indonesia (MPR-RI) in 2002 has recommended the DPR-RI and the President of the Republic of Indonesia to make changes to the Law Number 22 Year 1997 concerning Narcotics. Therefore, the Government and DPR-RI ratified and enacted Law Number 35 of 2009 concerning Narcotics, as an amendment to Law Number 22 of 1997. Based on this law, the institutional status of BNN became a Non-Ministerial Government Institution (LPNK). ) with a vertical structure to the Province and regency / city. In the Province the Provincial BNN was formed, and in the Regency / City the Regency / City BNN was formed Keywords : Legal Position. BNN. State administration